The assessment of the quality of public space on the example of Katowice and Bytom = Ocena jakości przestrzeni publicznej na przykładzie Katowic i Bytomia - Kossak-Jagodzińska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A well-designed public space is friendly to its users. There are several different research methods to evaluate its utility quality. This study analyses town market squares in Katowice and Bytom, and two commercial complexes in these cities: SCC in Katowice and Agora in Bytom (both include representative-public squares in their concepts).
Keywords: przestrzeń publiczna; ocena jakości; metoda PPS; koncepcja Halla; Katowice; Bytom; centrum handlowe; public space; quality assessment; PPS method; Hall's concept; market; shopping center